If x 1 and x 2 are distinct roots of x 2 − 6 x + 1 = 0 and S n = x 1 n + x 2 n , where n is a positive integer. Find the remainder of S 5 0 when divided by 5.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since x 1 and x 2 are roots of x 2 − 6 x + 1 = 0 , by Vieta's formula we have x 1 + x 2 = 6 and x 1 x 2 = 1 . And by Newton sums method, we have:
S 1 S 2 S n = x 1 + x 2 = 6 = x 1 2 + x 2 2 = ( x 1 + x 2 ) 2 − 2 x 1 x 2 = 3 4 = ( x 1 + x 2 ) S n − 1 − x 1 x 2 S n − 2 = 6 S n − 1 − S n − 2 for n ≥ 3
This implies that S n has a recurrence relation and its characteristic equation is:
r 2 − 6 r + 1 r ⟹ S n S 1 S 2 = 0 = 3 ± 8 = c 1 ( 3 + 8 ) n + c 2 ( 3 − 8 ) n = ( 3 + 8 ) c 1 + ( 3 − 8 ) c 2 = ( 3 + 8 ) 2 c 1 + ( 3 − 8 ) 2 c 2 = ( 1 7 + 6 8 ) c 1 + ( 1 7 − 6 8 ) c 2 where c 1 and c 2 are constants.
⟹ { S 1 : S 2 : 3 ( c 1 + c 2 ) + 8 ( c 1 − c 2 ) = 6 1 7 ( c 1 + c 2 ) + 6 8 ( c 1 − c 2 ) = 3 4
6 S 1 − S 2 : c 1 + c 2 = 2
S 1 : 3 ( c 1 + c 2 ) + 8 ( c 1 − c 2 ) 3 ( 2 ) + 8 ( c 1 − c 2 ) c 1 − c 2 ⟹ c 1 = 6 = 6 = 0 = c 2 = 1
Therefore,
S n S 5 0 S 5 0 = ( 3 + 8 ) n + ( 3 − 8 ) n = ( 3 + 8 ) 5 0 + ( 3 − 8 ) 5 0 ≡ 2 k = 0 ∑ 2 5 ( 2 k 5 0 ) 3 2 k ⋅ 8 k (mod 5) = 2 ( 3 5 0 + 8 2 5 ) (mod 5) = 2 ( 3 5 0 mod ϕ ( 5 ) + 8 2 5 mod ϕ ( 5 ) ) (mod 5) = 2 ( 3 5 0 mod 4 + 8 2 5 mod 4 ) (mod 5) = 2 ( 3 2 + 8 1 ) (mod 5) = 2 ( 1 7 ) (mod 5) = 4 (mod 5) Note that ( 2 k 5 0 ) is divisible by 5 for 1 ≤ k ≤ 2 4 Since g cd ( 3 . 5 ) = 1 , g cd ( 8 , 5 ) = 1 , Euler’s theorem applies. Euler’s totient function ϕ ( 5 ) = 4
Thanks so much. I appreciate it!
Log in to reply
Nice problem. I gotta use Vieta's, Newton's, recurrence and Euler's.
What are those blues..?
Log in to reply
In the last part of solution.
On apply vieta's formula, we have x 1 x 2 = 1 or x 2 = x 1 1
Since x 1 , x 2 are roots of the given equation so, they must satisfy the equation
Given equation can be written as
⟹ x 1 + x 1 1 = 6
S 1 ≡ x 1 + x 2 = 6
S 2 ≡ x 1 2 + x 2 2 = 3 4
S 3 ≡ x 1 3 + x 2 3 = 1 9 8
S 4 ≡ x 1 4 + x 2 4 = 1 1 5 4
S 5 ≡ x 1 5 + x 2 5 = 6 7 2 6
we notice the last digit starts repeated after a cycle of 4, therefore in order to find remainder of 50th power when divided by 5,
we only need to see last digit of the 2nd term of the cycle, which is 4 and hence on dividing by 5 we get remainder as 4 .
If you are curious: S 5 0 = 1 8 9 4 8 2 2 5 0 2 9 9 2 7 3 8 6 6 8 3 5 7 4 6 1 5 9 8 4 1 8 0 0 0 3 5 8 7 4
When you divide by 5, the remainder is 4
Problem Loading...
Note Loading...
Set Loading...
For x = x 1 and x = x 2
x 2 − 6 x + 1 = x 2 − x + 1 ( x 2 − x + 1 ) ( x + 1 ) x 3 = 0 (mod 5) = x 3 + 1 = 0 (mod 5) = − 1 (mod 5) ⟹ x 1 3 = x 2 3 = − 1 (mod 5)
And by vieta, we have x 1 + x 2 = 6 and x 1 x 2 = 1
Then, S 5 0 (mod 5) is S 5 0 = ( x 1 5 0 + x 2 5 0 ) = ( ( x 1 3 ) 1 6 × x 1 2 + ( x 2 3 ) 1 6 × x 2 2 ) (mod 5) S 5 0 = ( ( − 1 ) 1 6 × x 1 2 + ( − 1 ) 1 6 × x 2 2 ) (mod 5) S 5 0 = ( x 1 2 + x 2 2 ) = ( ( x 1 + x 2 ) 2 − 2 x 1 x 2 ) (mod 5) S 5 0 = ( ( 6 ) 2 − 2 × 1 ) (mod 5) S 5 0 = 3 4 (mod 5) S 5 0 = 4 (mod 5)